PELATIHAN PERANCANGAN ALAT PERMAINAN EDUKATIF (APE) BERBASIS BAHAN BEKAS UNTUK PENDIDIKAN ANAK USIA DINI (PAUD) SE-SIWALANKERTO SURABAYA - Aniendya Christianna (SHARE: Journal of Service Learning, 2013)
It takes a breakthrough to empower and synergize all the potential that already exists in society in order to achieve the service to child development as a whole, comprehensive and integrated. One of the very media that support the growth and development of children is EGT. Educative Game Tools now widely sold in the market with varying prices. In general, much of the education providers are still buying game tools to support children's learning. This of course will foster consumptive culture and weaken the educator's ability to be creative and innovative in providing a quality learning for children. Thus, the authors attempt to develop a training activity in order to encourage the creativity of Instructor/Mother of preschool children to design various kind of EGT from cheap and easily obtainable materials.